ANTS OF THE GENUS DOLICHODERUS (HYMENOPTERA: FORMICIDAE) FROM THE BALTIC AND ROVNO AMBERS - Dlussky G.M. (My University, 2002)
The genus Dolichodenis from the Baltic amber, Late Eocene, is revised. Four new species are described from the Baltic amber, and two new species are described from the Rovno amber. This is the first record of this genus from the Rovno amber.